European Socio-Economic Integration Challenges, Opportunities and Lessons Learned - Carayannis, Elias G.; Korres, George M.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2013)
Economic integration is one of the most noteworthy issues in international economic policy at the end of the twentieth century. The recent examples of the European Union (EU) and the North American Free Trade Association (NAFTA) have raised important questions about the economic integration process and the possible establishment of economic unions in other parts of the world.  Against the backdrop of the financial crisis in Europe and prospects of increasing integration in Asia, this volume showcases research from an international array of researchers to provide a basic understanding of the current issues, problems, challenges, and opportunities for achieving integration, addressing both empirical and theoretical aspects of such topics as monetary union, social policy reform and social union, public finance and technology policy.  The chapters in Part 1 are focused primarily on economic issues, while Part 2 covers on social policy, the welfare state, and political reforms, with a particular emphasis on the European Union.  Among the questions addressed: What are the main determinants and implications for socio-economic integration? How can economic policy influence the growth and integration process? Why is innovation important for regional economic development? What has been the policy response so far and what lessons have we learned from it? And finally, what are our action lines for the future?
Inflation Convergence in Europe -- Economic Integration and Convergence in the European Union -- The Mathematical Capital and its Economic Value -- Political Decision in a Game Theory Approach -- Economic Integration and Small States: Non-Traditional Benefits -- The Greek Crisis & Co.D.TRA (Code of Digital Transactions): Mobile Payments and the Global Info-Cash (GIC) -- Building Bridges in South Asia: Regional Cooperation Information Technologies and Opportunities for Integration -- Education Policy and Regional Convergence in European Union -- Innovation Process in the European Union: The Case of Galileo Project -- A Benchmarking Study for Human Capital in Europe -- Social Policy and Socio-Economic Integration in Europe -- Conversations with Civil Servants: East European Public Administration Reform in Search of Socio-Economic Development -- A New Methodological Approach of Job Requirement Assessment -- Critical Evaluation of the Greek Tourism Policy.
Keywords: Economic policy; Regional economics; Spatial economics; Development economics; Economic Policy; Regional/Spatial Science; Development Economics